intercultural dimension and the teaching of English in Portugal, The - Vieira, João Carlos Amorim da Costa Lopes (2011)
O presente trabalho propõe-se abordar a questão da cultura e o seu papel no ensino de Inglês Língua Estrangeira no ensino obrigatório em Portugal, nomeadamente no 2º e 3º ciclos do Ensino Básico, tendo em conta o contexto de globalização em que hoje vivemos e a necessidade de nos relacionarmos com outros povos. Neste sentido, realizámos um estudo baseado no levantamento de opiniões de alunos e professores sobre a dimensão cultural no ensino de Inglês e numa análise de conteúdo do programa de Inglês dos 2º e 3º ciclos de uma perspectiva intercultural. Este estudo mostra que, apesar de existirem elementos positivos no programa e atitudes de interesse e abertura por parte de professores e alunos perante a dimensão cultural, há ainda um longo caminho a percorrer, no que diz respeito à implementação de uma abordagem intercultural no ensino de Inglês em Portugal. ABSTRACT: This study aims to look at culture and its role in the English Language syllabus for the 2nd and 3rd Cycles of Basic Schooling in Portugal, taking into account the ever increasing need for peoples to interact with and relate to each other in an era of globalisation. To achieve our purposes, we have conducted a survey on the opinions of students and teachers about the cultural dimension of the teaching of English and we have analysed the content of the English syllabus of both the 2nd and 3rd cycles from an intercultural perspective. Our results show that, even though there are positive aspects in the syllabus and teachers and students show interest and openness towards the cultural dimension, there is still a long way to go before we can say there is an intercultural approach in the teaching of English in Portugal.